2012
DOI: 10.1024/1421-0185/a000065
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personality and Culture on the Job Demands-Control Model of Job Stress

Abstract: Abstract. Among the various work stress models, one of the most popular has been the job demands-control (JDC) model developed by Karasek (1979), which postulates that work-related strain is highest under work conditions characterized by high demands and low autonomy. The absence of social support at work further increases negative outcomes. This model, however, does not apply equally to all individuals and to all cultures. This review demonstrates how various individual characteristics, especially some person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…While there is at least some evidence for moderator effects of segmentation preferences on the relationship between WREA and relevant outcome variables, there is virtually none for personality traits, which is astonishing given that personality strongly impacts how employees experience work demands and whether they feel strained by them (Györkös et al, 2012). Personality traits influence emotion regulation strategies (Kokkonen & Pulkkinen, 2001), coping behaviors (Connor-Smith & Flachsbart, 2007), and how people respond to external stimuli (Bolger & Schilling, 1991).…”
Section: Current Researchmentioning
confidence: 99%
“…While there is at least some evidence for moderator effects of segmentation preferences on the relationship between WREA and relevant outcome variables, there is virtually none for personality traits, which is astonishing given that personality strongly impacts how employees experience work demands and whether they feel strained by them (Györkös et al, 2012). Personality traits influence emotion regulation strategies (Kokkonen & Pulkkinen, 2001), coping behaviors (Connor-Smith & Flachsbart, 2007), and how people respond to external stimuli (Bolger & Schilling, 1991).…”
Section: Current Researchmentioning
confidence: 99%
“…Even though personality traits predict several important work outcomes, the strength of these relationships is a function of the outcome considered, of the complexity of the work activity, and of the work context (Barrick & Mount, 2012). In further studies, the buffering role of personality on the relationship between situational and environmental factors and well-being at work may be valuable to investigate, as well as taking into account the role of culture (Györkos, Becker, Massoudi, de Bruin, & Rossier, 2012).…”
Section: Limitationsmentioning
confidence: 99%
“…For example, some of the Chinese traditional cultural values that originated from Confucian social ethics differ notably from those of Western societies, such as respect for authority, fatalism and a sense of powerlessness (Xie et al, ). Although a recent cross‐cultural JDC model review suggested that the model is generalizable across cultures, including China (Györkös, Becker, Massoudi, de Bruin, & Rossier, ), an extensive literature review of previous JDC studies using non‐Western blue‐collar samples (e.g. manufacturers) yielded mixed results.…”
Section: The Present Studymentioning
confidence: 99%